An Exploration of Graduate Students’ Career Transition Experiences - Wiesenberg, Faye; Aghakhani, Anoosha (Canadian Journal of Counselling and Psychotherapy, 2008)
The researchers explored the possible relationships between six specific influencing factors and the timing of a small group of graduate students’ movement through their program, using a short researcher-designed qualitative survey administered once to students at three points in their programs: entrance, mid-point, and exit. While the experience of moving through graduate school does not appear to be well addressed in the research literature, this study points to the relevance of these specific factors for this small group of graduate students. Suggestions for further research are given.